LAYANAN KONSELING PERORANGAN DALAM PRAKTEK KEBIDANAN - Sari, Kurnia (JURNAL FOKUS KONSELING, 2016)
Midwifery practice is medical treatment which related to an expectant mother, puerperal mother, health nursing of children under five, and small child. Ideally, midwife practice service includes mental and health service because both of them are influenced each other. Individual counseling service which is intergreted with midwifery practice will increase completness of service. Individual counseling service is a kind of service to aid patient with mental problem such as feeling trouble, while midwifery practice help to heal patient physical including bodily disease. Person life quality that getting physical trouble is determined by one feeling in accepting self-condition. Thus if people has no psychological problem, the patient who get health problem will not in trouble.Keywords: individual counseling service, midwifery practice.